Brand Image, Lifestyle dan Prestige terhadap Keputusan Pembelian Starbucks oleh Generasi Z - Ericko, Ericko; Marpaung, Fenny Krisna; Natasya, Natasya; Wilson Wijaya; Sherren Cokro; Christin Imelda Girsang (Journal of Management and Bussines (JOMB), 2026)
This study aims to analyze the influence of brand image, lifestyle, and prestige on Starbucks purchasing decisions by Generation Z. The research method used is quantitative research with an explanatory research approach. The population in this study were 1,229 students from the Faculty of Economics, Department of Management, Prima Indonesia University, in the 2019–2021 academic year, with a sample size of 93 respondents who consumed Starbucks. Data collection techniques were conducted through questionnaires, interviews, and documentation. Data analysis used multiple linear regression with the assistance of a statistical data processing program. The results showed that partially, brand image had a positive and significant effect on Starbucks purchasing decisions by Generation Z with a significance value of 0.001 < 0.05, lifestyle had a positive and significant effect on purchasing decisions with a significance value of 0.008 < 0.05, and prestige had a positive and significant effect on purchasing decisions with a significance value of 0.002 < 0.05. Simultaneously, brand image, lifestyle, and prestige had a positive and significant effect on Starbucks purchasing decisions by Generation Z with a significance value of 0.000 < 0.05. The conclusion of this study indicates that brand image, lifestyle, and prestige are factors that can increase Starbucks purchasing decisions among Generation Z.  Keywords: Brand Image, Generation Z, Purchasing Decisions, Lifestyle, Prestige